Bureaucratic virtue and the ministerial hierarchy - Christensen, Jørgen Grønnegård; Wang, Julie Grunnet; Opstrup, Niels (Politica, 2016)
Several cases have drawn attention to the interaction between ministers and civil servants. This is basically a principal-agent-problem. However, this problem has two sides: Agents’ usurpation of power vested in the principal and the principal’s use of the agent for political purposes that are illegitimate. Based on data collected under the auspices of the Bo Smith Commission a set of norms for correct bureaucratic behavior are identified. But how do civil servants handle these norms? A vignette analysis shows that civil servants have a differentiated approach to the norms and distinguish sharply between their legal obligations and the obligation to respect the truth and professional insight. Moreover, higher civil servants and civil servants in ministerial departments play a key role as guardians of the law.